Sistem Pakar Diagnosa Penyakit pada Ibu Hamil - Hendra Effendi (Sekolah Tinggi Manajemen Informatika dan Komputer PalComTech, 2020)
The high maternal mortality rate in the city of Palembang in 2017 reached 7 maternal deaths out of 27,876 live births largely due to ignorance regarding pregnancy issues and delays in handling. This expert system of diseases diagnosis in pregnant women is made to provide knowledge about diseases in pregnant women and its handling and prevention. The Naive Bayes Classifier method applied to this expert system is a simple probabilistic classification that calculates a set of probabilities by summing the frequency and combination of values from a given dataset. The final result of this study was an expert system of diseases diagnosis in pregnant women that can provide knowledge about diseases in pregnant women and its handling and prevention.